The Hungarian adaptation of the Motivation for Learning Music Questionnaire - Földi, Fanni; Józsa, Krisztián (Iskolakultúra, 2022)
On an international level, motivation for learning music is a widely researched area. The associations between music and motivation have been interpreted based on various theories of motivation, however, only a limited number of studies have focused on this area in Hungary so far. This study describes the adaptation of the Motivation for Learning Music (MLM) questionnaire, which is based on the self-determination theory. Contrary to international studies, Hungarian research mainly focuses on school music lessons, therefore, little is known about the relationship between learning musical instruments and motivation. The Hungarian version of the original questionnaire which was developed by Comeau et al. (2019) was completed by 151 students (age: Mean=14.7 years, SD=2.49) using the Google Form platform. The questionnaire consists of 25 5-point Likert-type items; its five subscales are amotivation, external regulation, introjection, identification and integration, and intrinsic motivation. The study describes the psychometric properties (factorial validity and reliability) of the Hungarian questionnaire, examines its inter-factor correlations, and compares the music learning motivation of younger and older students of the sample. Confirmatory factor-analysis indicated a good fit between the data and the theoretical model. Cronbach’s α was at least 0.8 or above for each factor. Inter-factor correlations showed the expected pattern. Significant differences were found in three types of motivation between 10–14-year-olds and 15–18-year-olds; introjection, identification and integration, and intrinsic motivation were more characteristic of the older age group. As a result of the adaptation, a new Hungarian instrument is available to explore students’ motivation to learn musical instruments. The questionnaire allows researchers to launch international comparative studies.